2019
DOI: 10.1016/j.jviromet.2019.113729
|View full text |Cite
|
Sign up to set email alerts
|

Common vole (Microtus arvalis) and bank vole (Myodes glareolus) derived permanent cell lines differ in their susceptibility and replication kinetics of animal and zoonotic viruses

Abstract: Common vole (Microtus arvalis) and bank vole (Myodes glareolus) derived permanent cell lines differ in their susceptibility and replication kinetics of animal and zoonotic viruses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…Further in vitro studies are needed to determine whether heterologous bank voles evolutionary lineages could support PUUV isolation and/or infection. These future investigations may profit from the recent establishment of permanent bank vole cell lines from different evolutionary lineages of the bank vole (29).…”
Section: Discussionmentioning
confidence: 99%
“…Further in vitro studies are needed to determine whether heterologous bank voles evolutionary lineages could support PUUV isolation and/or infection. These future investigations may profit from the recent establishment of permanent bank vole cell lines from different evolutionary lineages of the bank vole (29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations indicated that VeroE6 cell adaptation of PUUV Kazan strain results in the inability of the adapted strain to infect the bank vole reservoir [8]. The recent development of bank vole-derived primary or permanent cell lines may allow the isolation of reservoir-adapted PUUV strains [9][10][11][12].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This endemic region was also again heavily affected by the hantavirus outbreak year 2019 [25]. Here, we aimed to isolate a Central European PUUV strain from bank voles in the district of Osnabrück using standard VeroE6 cells and the recently established Carpathian lineage bank volederived kidney cell line (MGN-2-R [10]). Complete genome determination by shot-gun and hybrid-capture-mediated highthroughput sequencing (HTS) was used to follow the potential adaptation of the PUUV isolates in VeroE6 and reservoir cell lines.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations